VANCOUVER ISLAND HEALTH AUTHORITY (VIHA) IN HOUSE PERIOPERATIVE NURSING PROGRAM - Christensen, Fern (Operating Room Nurses Association of Canada Journal, 2005)
The Vancouver Island Health Authority (VIHA) in liaison with the University of Victoria (UVIC) offers an introduction to Perioperative Nursing Program to 4th Year undergraduate nursing students. The aim of this program is to help recruit Registered Nurses to the Operating Room. It has been advantageous to the recruitment and retention of nurses graduating from UVIC. Its importance is increased by the fact that a significant quantity of Victoria’s perioperative nurses will be retiring in the next few years. Due to the high cost of nursing education and the financial investment that has already been committed by nursing students, the Perioperative nursing program is free to the student as the program can be included, for the successful candidate, as part of the UVIC nursing course. The intention is to encourage participation by reducing the financial burden, stress, and anxiety for the new graduate who intends to specialize. In return, the student is required to work in the VIHA for a minimum of one year, thus supporting the retention efforts of the hospital. For eligible nursing students, this program provides access to extensive perioperative nursing experience. Over the course of 3 months they are exposed to extensive theory in a classroom setting as well as clinical practice through a preceptorship program. The mentoring relationships that develop between perioperative nurses and students lead to meaningful relationships and professional growth for staff. The perioperative focus of the program improves the knowledge and skill set of nursing students. The intent is to increase nursing student’s interest in pursuing a career as a perioperative nurse and to help ensure continued growth of the perioperative nursing profession in Victoria.